The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1074/jbc.m705937200
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Induces Estrogen-related Receptor α Gene Expression and Chromatin Structural Changes in Estrogen Receptor (ER)-positive and ER-negative Breast Cancer Cells

Abstract: Estrogen-related receptor ␣ (ERR␣), a member of the nuclear receptor superfamily, is closely related to the estrogen receptors (ER␣ and ER␤). The ERR␣ gene is estrogen-responsive in several mouse tissues and cell lines, and a multiple hormone-response element (MHRE) in the promoter is an important regulatory region for estrogen-induced ERR␣ gene expression. ERR␣ was recently shown to be a negative prognostic factor for breast cancer survival, with its expression being highest in cancer cells lacking functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 83 publications
1
14
0
Order By: Relevance
“…These findings support previous studies which demonstrate direct inhibitory effects of E2 on PEPCK expression via PGC1α (peroxisome proliferator activated receptor gamma co-activator 1 alpha) [35], [36] and studies showing estrogens administration to ob/ob mice reduces G6Pase expression [37]. GSK3β was elevated in the ArKO compared to WT and reduced upon E2 treatment at 3months, but not evident at 6 months of age.…”
Section: Discussionsupporting
confidence: 91%
“…These findings support previous studies which demonstrate direct inhibitory effects of E2 on PEPCK expression via PGC1α (peroxisome proliferator activated receptor gamma co-activator 1 alpha) [35], [36] and studies showing estrogens administration to ob/ob mice reduces G6Pase expression [37]. GSK3β was elevated in the ArKO compared to WT and reduced upon E2 treatment at 3months, but not evident at 6 months of age.…”
Section: Discussionsupporting
confidence: 91%
“…Cells derived from human breast tumor tissues were analyzed on HTS affymetrix gene chip resulted with an up-regulation of gene expression when treated by estrogen and even more by ICI-182,780 [58]. Modulation by ICI-182,780 resulted with up regulation of quinine reductase in MCF-7 cells [59], ERRα in SKBR3 cells [60] and spinophilin in hippocampus neurons [61]. The promoter activation by ICI-182,780 is proposed to act via ER binding on AP-1 sites, but not via ERE [62].…”
Section: Discussionmentioning
confidence: 99%
“…In this alternative view, some movements result in the co-localization ("gene kissing") of sets of genes widely separated before stimulation, allowing their spatial co-regulation. One example put forward to support this view described rapid large-scale movements of specific estrogen-inducible genes and of the CTs carrying these genes (Hu et al 2008), but this finding could not be confirmed by carefully executed subsequent studies (Kocanova et al 2010).…”
Section: Stability and Dynamics Of Higher-order Chromatin Arrangementsmentioning
confidence: 94%